Negative Gossip: A Systematic Review and Future Research Directions - Erika Fajar Subhekti; Fiona Niska Dinda Nadia (Dinasti International Journal of Education Management And Social Science, 2024)
This study is a systematic and comprehensive literature review discussing the concept of negative gossip and its role in providing recommendations for future research. The study also explores the opportunities available for future scholars to develop and expand the existing literature in this field. The research concludes that negative gossip involves the dissemination of harmful or disadvantageous information about others, which can impact relationships, emotional well-being, and their reputation. Although the concept is still in its early stages with various definitions, some studies have analyzed the variables affecting negative gossip at both individual and organizational levels. This review examines how mechanisms and contexts support the outcomes of negative gossip and emphasizes the need for further research in empirical studies, methods, and theoretical foundations required for advancing knowledge in this area.